1969
DOI: 10.1111/j.1651-2227.1969.tb04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Cystathioninuria

Abstract: Increased urinary excretion of cystathionine has been reported in 6 patients and was associated in 5 of them with mental retardation. This patient group is interpreted as having an inborn error of metabolism due to a disturbance in the metabolic breakdown of cystathionine (primary cystathioninuria) 1(4). Several reports of increased urinary excretion of cystathionine in children in combination with various diseases, eg. pyridoxine deficiency, neuroblastoma galactosaemia and hepatoblastoma have been published (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…With regard to leukemia and tumors, our results are in accord with observations made by Geiser and Efron [4]. However, we expected a more frequent occurrence of secondary cystathioninuria in patients with liver diseases and hereditary metabolic disorders in view of the published data [1,8,10,11].…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…With regard to leukemia and tumors, our results are in accord with observations made by Geiser and Efron [4]. However, we expected a more frequent occurrence of secondary cystathioninuria in patients with liver diseases and hereditary metabolic disorders in view of the published data [1,8,10,11].…”
Section: Discussionsupporting
confidence: 95%
“…The same is true for increased transaminase activities (2/7~29% vs. 10/37 ~ 27%). This agrees with the results of other authors [1,8,11]. Thus, it may be concluded that hepatomegaly and increased transaminases are frequent findings in patients with secondary cystathioninuria, but not vice versa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations